Immunophysical Evaluation of the Initiating Step in the Formation of the Membrane Attack Complex - Zewde, Nehemiah; Mohan, Rohith R.; Morikis, Dimitrios (Frontiers in Physics, 2018)
The complex between complement system proteins C5b and C6 is the cornerstone for the assembly of the membrane attack complex (MAC, also known as C5b6789n). MAC is the terminal product of three converging pathways of the complement system and functions as a pore forming complex on cell surfaces, as a response of the immune system in fighting pathogens. However, when proper regulation of the complement system is compromised, MAC also attacks host tissues and contributes to several complement-mediated autoimmune diseases. We performed a molecular dynamics and electrostatics study to elucidate the mechanism of interaction between C5b and C6 and the formation of the C5b6 complex. The C5b-C6 interface consists of three binding sites stabilized predominantly by van der Waals interactions, and several critical salt bridges and hydrogen bonds. We discuss differences between domains C5d and C3d that lead to mono-functionality of C5d in acting as the scaffold for MAC formation, as opposed to dual functionality of C3d in acting as an opsonin for phagocytosis and as a link between innate and adaptive immunity, based on a comparative sequence, structural, and physicochemical analysis. We also extended our analysis to pathway dynamics to demonstrate the significance of consumption-production rates of C5b, C6 and C5b6 that lead towards MAC formation. Finally, we propose that C5d is a target for drug discovery, aiming to the inhibition of the MAC formation in autoimmune diseases originating from MAC-mediated host cell lysis.